Pedestrians' and Cyclists' Effect on the Capacity of the Right Turn Movement at Signalized Intersections: An Empirical Pilot Study - Aagaard, Pierre E.; Jørgensen, Niels O.; Rysgaard, Rikke; Sørensen, Henning (Proceedings from the Annual Transport Conference at Aalborg University, 1998)
The use of bicycles as a means of transport in journey-to-work trips is widespread in North West Europe. In countries such as The Netherlands, Germany and Denmark there is a tradition for research concerning bicycle traffic. For reasons of safety and convenience special cycle tracks alongside vehicle lanes are often provided where possible. Where such tracks exist through signalized intersections cyclists create problems for right turning vehicles in the same manner as do pedestrians using a pedestrian crossing. Cyclists are often much more numerous than pedestrians along main arterials. Therefore, there is a need for a method for estimating the effect on capacity of the volume of cycle traffic. Only a few methods exist (e.g. Tepley (1990)).